Copy number profiling of adult relapsed B‐cell precursor acute lymphoblastic leukemia reveals potential leukemia progression mechanisms. Issue 11 (26th August 2017) - Ribera, Jordi; Zamora, Lurdes; Morgades, Mireia; Mallo, Mar; Solanes, Neus; Batlle, Montserrat; Vives, Susana; Granada, Isabel; Juncà, Jordi; Malinverni, Roberto; Genescà, Eulàlia; Guàrdia, Ramon; et al.
Abstract: The outcome of relapsed adult acute lymphoblastic leukemia (ALL) remains dismal despite new therapeutic approaches. Previous studies analyzing relapse samples have shown a high degree of heterogeneity regarding gene alterations without an evident relapse signature. Bone marrow or peripheral blood samples from 31 adult B‐cell precursor ALL patients at first relapse, and 21 paired diagnostic samples were analyzed by multiplex ligation probe‐dependent amplification (MLPA). Nineteen paired diagnostic and relapse samples of these 21 patients were also analyzed by SNP arrays. A trend to acquire homozygous CDKN2A/B deletions and a significant increase in the number of copy number alterations (CNA) was observed from diagnosis to first relapse. Evolution from an ancestral clone was the main pattern of clonal evolution. Relapse samples were extremely heterogeneous regarding CNA frequencies. However, CDKN2A/B, PAX5, ETV6, ATM, IKZF1, VPREB1, and TP53 deletions and duplications of 1q, 8q, 17q, 21, X/Y PAR1, and Xp were frequently detected at relapse. Duplications of genes involved in cell proliferation, drug resistance and stem cell homeostasis regulation, as well as deletions of KDM6A and STAG2 genes emerged as specific alterations at relapse. Genomics of relapsed adult B‐cell precursor ALL is highly heterogeneous, although some recurrent lesions involved in essential pathways deregulation were frequently observed. Selective and simultaneous targeting of these deregulated pathways may improve the results of current salvage therapies.